2019
DOI: 10.3389/fpls.2019.01248
|View full text |Cite
|
Sign up to set email alerts
|

Red to Brown: An Elevated Anthocyanic Response in Apple Drives Ethylene to Advance Maturity and Fruit Flesh Browning

Abstract: The elevation of anthocyanin contents in fruits and vegetables is a breeding target for many crops. In some fruit, such as tomato, higher anthocyanin concentrations enhance storage and shelf life. In contrast, highly anthocyanic red-fleshed apples (Malus x domestica) have an increased incidence of internal browning flesh disorder (IBFD). To determine the mechanisms underlying this, ‘Royal Gala’ cultivar apples over-expressing the anthocyanin-related transcription factor (TF) MYB10 (35S:MYB10), which produces f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…We determined that many TFs, such as MYB, bHLH, WRKY, and ERF, might regulate key genes in the biosynthesis pathways of chlorogenic acid and luteolin in L. japonica. Previous research suggests that TFs in the MYB and bHLH families might participate in the biosynthesis of chlorogenic acid (Espley et al, 2019;Liu et al, 2019;Qi et al, 2019;Wang et al, 2019). Therefore, we used the motif analysis tool to analyze possible regulatory factors upstream of key enzyme genes and observed that MYB, WRKY, and ERF motifs were significantly enriched.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that many TFs, such as MYB, bHLH, WRKY, and ERF, might regulate key genes in the biosynthesis pathways of chlorogenic acid and luteolin in L. japonica. Previous research suggests that TFs in the MYB and bHLH families might participate in the biosynthesis of chlorogenic acid (Espley et al, 2019;Liu et al, 2019;Qi et al, 2019;Wang et al, 2019). Therefore, we used the motif analysis tool to analyze possible regulatory factors upstream of key enzyme genes and observed that MYB, WRKY, and ERF motifs were significantly enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the GBSS gene that is responsible for the synthesis of starch was mutated using Cas9 in potatoes. An increase in amylopectin levels was observed in mutant lines [126]. The SnLazy1 locus, known as the Lazy1 ortholog in tomatoes, was manipulated by CRISPR/Cas9 with effective heritability of the snlazy-1 allele, and mutants showed a downward pattern of stem development [127].…”
Section: Use Of Crispr/cas9 For Improvement Of Yield and Qualitymentioning
confidence: 99%
“…A ground cherry of a wild variety of tomatoes yielded higher and larger fruits [129]. Additionally, in apples, a mutation of PPO was reflected as transgene-free using Cas9, which is appropriate for human consumption [126]. The production of seedless fruit is always the primary goal of any breeding plan.…”
Section: Use Of Crispr/cas9 For Improvement Of Yield and Qualitymentioning
confidence: 99%
“…Similarly, the starch synthase GBSS gene has been mutated in potato via CRISPR/Cas9. The mutated lines showed reduced amylose levels and an increased concentration of the amylose/amylopectin ratio [122]. Furthermore, the SnLazy1 locus, which is the tomato ortholog of Lazy1, was edited by CRISPR/Cas9 in Solanum nigra, with successful inheritance of the removal of two separate snlazy1-cr alleles and the production of plants with stem development in a relatively downward direction [123].…”
Section: Improvement In Yield and Quality Via Crispr/cas9 And Crispr/mentioning
confidence: 99%
“…Another group investigated a wild-type species of tomato called groundcherry (Physalis pruinosa) that produces a high yield of large fruits [39]. In addition, the PPO mutation in apples can be considered transgene free using CRISPR/Cas9 and could easily be applicable worldwide [122]. CRISPR/Cas9 is committed to the development of seedless fruits through the modification/mutation of genes responsible for seed formation.…”
Section: Improvement In Yield and Quality Via Crispr/cas9 And Crispr/mentioning
confidence: 99%